PELATIHAN PEMBUATAN WEBSITE CARRD.CO SEBAGAI MEDIA PERSONAL BRANDING UNTUK PEMUDA DI DESA SERANG - Irham Maulana; Taufiqurahman Taufiqurahman (Universitas Islam 45 Bekasi, 2022)
Along with the development of increasingly unstoppable technological advances everyone must think harder to keep up with the times plus the outbreak of the covid-19 virus that changes formal education in online learning. In the current era there are still many people applying for jobs by making written documents in the middle of the digitalization era, especially in the creation of curriculum vitae to apply for jobs. Many things change especially in terms of publication media from print media form to digital form. Non-formal education that exists still does not feel the maximum results in the community. The purpose of this program is to strive to improve the ability to make documents with existing facilities in the community, especially problems in typing and publication. Now there are many platforms that provide media publication of documents for free and this is where the role of students to direct and educate about publication digitally. This program is divided into two sessions, the first is Microsoft Word training to create cover letters, curriculum vitae and certificates and then continued with the creation of One-page site as a publication media. This program is held as many as six times online meetings with zoom meetings. In the implementation of the program participants are led to be able to understand the material provided by making the same thing with the creativity of each result participants are able to make cover letters, curriculum vitae, certificates and also carrd.co website. The results of this program require participants to be able to make a digital job application and publish it into digital media in the form of a website.